PEMBANGUNAN HUKUM BERBASIS BUDAYA LOKAL - Paisol Burlian (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2021)
In general, people understand culture in the form of works of art only. Whereas cultural understanding also involves attitudes, behaviors, and opinions that are sourced from the values ​​that live in society. Each sphere of society can have its own values, it may also have several values ​​that are different from one another. In such circumstances, action or agreement is often needed so that attitudes, behaviors and opinions show togetherness in society. Attitudes and behavioral opinions that stem from making the values ​​of the community that are embraced and having them establish rules in order to base human relations, relations between people and society. humans around. Even the relationship between the private and public with the natural environment, which is bound or strengthened by physical sanctions and is often followed by religious-magical ties.